Silver as Bridewealth - An Interpretation of Viking Age Silver Hoards on Gotland, Sweden - Burström, Mats (Current Swedish Archaeology, 1993)
A remarkably large number of Viking Age silver hoards have been found on the island of Gotland in the Baltic Sea. The reasons for this richness of finds have been the subject of much debate. This article presents an interpretation that has not been previously discussed. According to this, silver was a prestige valuable which was transferred as bridewealth. This interpretation is based on the settlement situation on Gotland during the Viking Age and on a hypothesis regarding what kind of policies for land division this situation necessitated.